2010
DOI: 10.3390/molecules15129184
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds of Young Wines from Cabernet Sauvignon, Cabernet Gernischet and Chardonnay Varieties Grown in the Loess Plateau Region of China

Abstract: In order to elucidate the aroma components of wine produced in the Loess Plateau region of China, volatile compounds of young wines from Cabernet Sauvignon, Cabernet Gernischet and Chardonnay varieties grown in the new ecological region were investigated for the first time in this research. Among the volatile compounds analyzed by HS-SPME with GC-MS, a total of 45, 44 and 42 volatile compounds were identified and quantified in Cabernet Sauvignon, Cabernet Gernischet and Chardonnay wines, respectively. In the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 43 publications
12
109
3
2
Order By: Relevance
“…In our study, 18 alcohols have been identified in the analysed Vranec wines (Table 2). This volatile fraction was mainly composed of five compounds present in highest amount: isoamyl alcohol, 2-methyl-1-butanol, phenylethyl alcohol, isobutyl alcohol and 1-hexanol, which is in agreement with literature data (Jiang & Zhang, 2010;Patel & Shibamoto, 2003;Schreier, Drawert, & Junder, 1976). These compounds are usually formed by the yeast, from the sugars or amino acids present in the grape mash (Ivanova et al, 2012).…”
Section: Alcoholssupporting
confidence: 78%
“…In our study, 18 alcohols have been identified in the analysed Vranec wines (Table 2). This volatile fraction was mainly composed of five compounds present in highest amount: isoamyl alcohol, 2-methyl-1-butanol, phenylethyl alcohol, isobutyl alcohol and 1-hexanol, which is in agreement with literature data (Jiang & Zhang, 2010;Patel & Shibamoto, 2003;Schreier, Drawert, & Junder, 1976). These compounds are usually formed by the yeast, from the sugars or amino acids present in the grape mash (Ivanova et al, 2012).…”
Section: Alcoholssupporting
confidence: 78%
“…The concentrations of nonanal determined in the wines ranged from 22.4 μg/L in Seyval blanc to 34.1 μg/L in St. Pepin (Table 3). In contrast, nonanal concentration has been reported to range from 1 μg/L [28] to 19 μg/L [29] in V. vinifera Chardonnay. Similarly, trans,cis-2,6-nonadienal is rarely reported in the volatile compound profile of wines from V. vinifera varieties; a recent study indicated that trans-2,cis-6-nonadienal was not detected in any of 18 Spanish wines [28].…”
Section: Compounds and Other Fadpmentioning
confidence: 94%
“…A volatile compound contributes to the aroma when its concentration in the wine is above the perception threshold, therefore odorants with odor activity value (OAV)  1 can be perceived (Guth, 1997;Jiang and Zhang, 2010;Juan et al, 2012;Welke et al, 2014). Capone et al (2013) identified 51 volatile compounds in Negroamaro red wines, and of these, only 18 components were perceived as active odorants (OAV  1).…”
Section: Introductionmentioning
confidence: 99%